Intestinal Microbes in Autoimmune and Inflammatory Disease - Wu, Wan-Jung H.; Zegarra-Ruiz, Daniel F.; Diehl, Gretchen E. (Frontiers in Immunology, 2020)
Autoimmune diseases and chronic inflammatory disorders are characterized by dysregulated immune responses resulting in excessive and uncontrolled tissue inflammation. Multiple factors including genetic variation, environmental stimuli, and infection are all thought to contribute to continued inflammation and pathology. Current evidence supports the microbiota as one such factor with emerging data linking commensal organisms to the onset and progression of disease. In this review, we will discuss links between the microbiota and specific diseases as well as highlight common pathways that link intestinal microbes with multiple autoimmune and inflammatory diseases.